Deepened winter snow cover enhances net ecosystem exchange and stabilizes plant community composition and productivity in a temperate grassland. (25th March 2020) - Li, Ping; Sayer, Emma J.; Jia, Zhou; Liu, Weixing; Wu, Yuntao; Yang, Sen; Wang, Chengzhang; Yang, Lu; Chen, Dima; Bai, Yongfei; Liu, Lingli
Abstract: Global warming has greatly altered winter snowfall patterns, and there is a trend towards increasing winter snow in semi‐arid regions in China. Winter snowfall is an important source of water during early spring in these water‐limited ecosystems, and it can also affect nutrient supply. However, we know little about how changes in winter snowfall will affect ecosystem productivity and plant community structure during the growing season. Here, we conducted a 5‐year winter snow manipulation experiment in a temperate grassland in Inner Mongolia. We measured ecosystem carbon flux from 2014 to 2018 and plant biomass and species composition from 2015 to 2018. We found that soil moisture increased under deepened winter snow in early growing season, particularly in deeper soil layers. Deepened snow increased the net ecosystem exchange of CO2 (NEE) and reduced intra‐ and inter‐annual variation in NEE. Deepened snow did not affect aboveground plant biomass (AGB) but significantly increased root biomass. This suggested that the enhanced NEE was allocated to the belowground, which improved water acquisition and thus contributed to greater stability in NEE in deep‐snow plots. Interestingly, the AGB of grasses in the control plots declined over time, resulting in a shift towards a forb‐dominated system. Similar declines in grass AGB were also observed at three other locations in the region over the same time frame and are attributed to 4 years of below‐average precipitation during the growing season. By contrast, grass AGB was stabilized under deepened winter snow and plant community composition remained unchanged. Hence, our study demonstrates that increased winter snowfall may stabilize arid grassland systems by reducing resource competition, promoting coexistence between plant functional groups, which ultimately mitigates the impacts of chronic drought during the growing season. Abstract : Winter snowfall is a critical water source for plant growth during early spring, especially in water‐limited grasslands. However, we know little about how changes in winter snowfall will affect ecosystem productivity and plant community structure during the growing season. Our 5‐year snow manipulation experiment showed that deepened snow enhanced net ecosystem CO2 exchange and resulted in greater belowground biomass allocation by increasing growing season water availability, especially in deep soils. Consequently, deep snow maintained the coexistence of plant functional groups (grasses and forbs), and stabilized plant community composition and productivity under a changing environment.